THE INFLUENCE OF LOCAL IMMUNE SYSTEM FACTORS ON THE DEVELOPMENT OF ORAL DISEASES IN PATIENTS WITH CHRONIC RENAL FAILURE (World Bulletin of Public Health, 2024)
Chronic renal failure (CRF) is a very serious medical, social and economic problem. This is determined both by the steady increase in the number of patients with CKD, and by the high cost of treatment and unfavourable labour prognosis. The damage of various systems of the organism in CKD is a consequence of a number of reasons, among which the most common are uremic intoxication, disturbance of water-electrolyte balance, bone and mineral metabolism, development of concomitant heart failure, immunological disorders, there are a number of other mechanisms that are not sufficiently studied. In a number of studies it has been shown that prolonged course of CKD leads to the development of fibrotic changes in the interstitial tissue of various organs
Keywords: chronic renal failure; periodontitis; lactoferrin; chronic kidney disease